A Practical Green Visit to the Functionalized [1, 2, 4]Triazolo[5, 1‐b]quinazolin‐8(4H)one Scaffolds Using the Group‐Assisted Purification (GAP) Chemistry and Their Pharmacological Testing. Issue 3 (22nd January 2019) - Patel, Divyang M.; Vala, Ruturajsinh M.; Sharma, Mayank G.; Rajani, Dhanji P.; Patel, Hitendra M.
Abstract: Herein, we established a straightforward synthetic route for biological relevant [1, 2, 4]triazolo[5, 1‐ b ]quinazolin‐8(4 H )one scaffolds using the group‐assisted purification (GAP) chemistry via one‐pot and three component reaction of 3‐Amino‐5‐methylthio‐1H‐1, 2, 4‐triazole (1), Aryl aldehyde(2 a–g), and 1, 3‐cyclodione(3 a–b) using L‐proline and aqueous ethanol (1:1, v/v) as green catalyst and reaction media respectively. This work shows some key features such as practical low Environment factor (E‐factor) values, excellent atom economy, reaction mass efficiency, mild reaction condition, metal‐free synthesis, and no use of column chromatography. In preliminary biological screening, the compounds, 2‐(methylthio)‐9‐(4‐nitrophenyl)‐5, 6, 7, 9‐tetrahydro‐[1, 2, 4]triazolo[5, 1‐ b ]quinazolin‐8(4 H )‐one (4 i) and 6, 6‐dimethyl‐2‐(methylthio)‐9‐(pyridin‐4‐yl)‐5, 6, 7, 9‐tetrahydro‐[1, 2, 4]triazolo[5, 1‐ b ]quinazolin‐8(4 H )‐one (4 l) were found most potent against Gram‐negative bacteria ( E. coli ) than the standard drugs ampicillin and chloramphenicol. Moreover, compounds 2‐(methylthio)‐9‐phenyl‐5, 6, 7, 9‐tetrahydro‐[1, 2, 4]triazolo[5, 1‐ b ]quinazolin‐8(4 H )‐one(4 a) and 9‐(4‐methoxyphenyl)‐6, 6‐dimethyl‐2‐(methylthio)‐5, 6, 7, 9‐tetrahydro‐[1, 2, 4]triazolo[5, 1‐ b ]quinazolin‐8(4 H )‐one(4 f) exhibited excellent potency in comparison with the standard drugs ampicillin, chloramphenicol, and ciprofloxacin against Gram‐positive bacteria ( S. aeruginosa and S. pneumoniae ). In antifungal screening compounds, 9‐(4‐methoxyphenyl)‐2‐(methylthio)‐5, 6, 7, 9‐tetrahydro‐[1, 2, 4]triazolo[5, 1‐ b ]quinazolin‐8(4 H )‐one(4 e) and 2‐(methylthio)‐9‐(4‐nitrophenyl)‐5, 6, 7, 9‐tetrahydro‐[1, 2, 4]triazolo[5, 1‐ b ]quinazolin‐8(4 H )‐one(4 i) efficiently inhibited C. albicans fungi strain than that of standard drug griseofulvin. Noteworthy compounds 6, 6‐dimethyl‐2‐(methylthio)‐9‐phenyl‐5, 6, 7, 9‐tetrahydro‐[1, 2, 4]triazolo[5, 1‐ b ]quinazolin‐8(4 H )‐one(4 b), 9‐(4‐chlorophenyl)‐6, 6‐dimethyl‐2‐(methylthio)‐5, 6, 7, 9‐tetrahydro‐[1, 2, 4]triazolo[5, 1‐ b ]quinazolin‐8(4 H )‐one(4 d), and 2‐(methylthio)‐9‐(pyridin‐4‐yl)‐5, 6, 7, 9‐tetrahydro‐[1, 2, 4]triazolo[5, 1‐ b ]quinazolin‐8(4 H )‐one(4 k) were exhibited better potency against M. Tuberculosis . Abstract : Synopsis By holding the green chemistry concept, we explored one‐pot synthesis [1, 2, 4]triazolo[5, 1‐ b ]quinazolin‐8(4 H )one scaffolds. Moreover, all the newly synthesized compounds were tested for their antimicrobial and anti tuberculosis activities. Noteworthy, majority of compounds were exhibited better antimicrobial and anti tuberculosis activities.